2000
DOI: 10.1088/0953-8984/12/5/317
|View full text |Cite
|
Sign up to set email alerts
|

Blue-green emission of Pr3+ions in LiNbO3

Abstract: The emission properties of the 3 P0 state of praseodymium ions in lithium niobate crystal have been studied. Blue-green emission at 510 nm corresponding to the 3 P0 3 H4 transition in Pr3+ :LiNbO3 crystals was generated after direct and up-conversion excitation with orange and infrared radiation around 920 nm. The up-conversion mechanisms were shown to be energy transfer and excited state absorption for orange and infrared excitation, respectively. The processes responsible for non-radiative relaxation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…A system, which is pumped in the IR region can emit in the VIS as well as in the UV region. Recently a great attention has been paid to the trivalent lanthanide ions Pr 3+ , Nd 3+ , Ho 3+ , Er 3+ , Tm 3+ , which can perform energy transformation by up-conversion in a wide range between 380 and 750 nm [15,77,78]. In the common case a two-photon absorption (TPA) process and an excited state absorption (ESA) process can occur in parallel in the up-conversion [78].…”
Section: Luminescence In the System Ln 3+ :Linbo 3 :Wgmentioning
confidence: 99%
“…A system, which is pumped in the IR region can emit in the VIS as well as in the UV region. Recently a great attention has been paid to the trivalent lanthanide ions Pr 3+ , Nd 3+ , Ho 3+ , Er 3+ , Tm 3+ , which can perform energy transformation by up-conversion in a wide range between 380 and 750 nm [15,77,78]. In the common case a two-photon absorption (TPA) process and an excited state absorption (ESA) process can occur in parallel in the up-conversion [78].…”
Section: Luminescence In the System Ln 3+ :Linbo 3 :Wgmentioning
confidence: 99%
“…(6) The ETU process has been proposed to follow the following path: 1 D 2 + 1 D 2 -1 G 4 + 3 P 2 +DE e.g. [13,14]. The energy mismatch DE is minimized by selecting the lowest Stark level of the 1 D 2 manifold (16,380 cm À1 ) and the highest levels of the 1 G 4 and 3 P 2 manifolds (10,219 and 22,411 cm À1 , respectively), and DE are found to be 130 cm À1 .…”
Section: Article In Pressmentioning
confidence: 99%
“…The importance of the phenomenon of upconversion is due to two facts: it is of scientific interest, because it contributes to the spectral characterization of a laser crystal and it can be useful in principle for the generation of short wavelength emission without having to rely on UV excitation that can have deleterious and secondary effects (such as creation of color centers and excitation of deep traps) on the laser materials. Upconversion that leads to blue ( 3 P 0 ) emission when pumping with red light into the lower energy levels has been observed in several systems [12][13][14][15][16][17]. Malinowski et al [12] have studied the upconversion into the 3 P 0 level of Pr 3+ :YAlO 3 following excitation into the 1 D 2 level.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that in LiNbO 3 :Pr 3+ the main channel of radiative deexcitation is through the 1 D 2 state and that luminescence from the 3 P 0 state is very weak and its decay is very fast. It was concluded in [11] that this unusual optical behavior of Pr 3+ ions in LiNbO 3 is related to the very low position of the 3 P 0 level which allows for nearly resonant cross relaxation via 1 G 4 levels.…”
Section: Introductionmentioning
confidence: 99%